Porphyrin photosensitizer distribution mechanisms in blood serum - Yakavets, Ilya V.; Yankovsky, Igor V.; Barysau, Kiryl N.; Jukov, Konstantin A.; Khludeyev, Ivan I.; Bolotine, Lina N.; Zorin, Vladimir P. (Journal of the Belarusian State University. Ecology, 2018)
A new fluorescent technique to monitor the distribution processes of non-polar porphyrin photosensitizer temoporfin (mTHPC) between main blood serum proteins has been described. The technique proposed includes the use of cyclic oligosaccharides (cyclodextrins) to prevent aggregation of the compound and to quantitatively estimate the main characteristics of mTHPC binding to the serum proteins. To determine the mTHPC affinity to transport serum proteins we have analysed the processes of mTHPC binding to methyl-β-cyclodextrin in serum proteins solutions (human serum albumin, low and high density lipoproteins). The obtained titration curves and previously determined binding constants values for the mTHPC association with methyl-β-cyclodextrin process were used to estimate relative mTHPC affinity to main transport serum proteins. The resulting values of the integrated distribution coefficients were as follows: 2,6 (mg/ml)-1 for human serum albumin, 4,8х102 (mg/ml)-1 for low density lipoproteins and 1,0х103 (mg/ml)-1 for high density lipoproteins. The ratios of mTHPC distribution coefficients in plasma compounds were in a good accordance with the data obtained by means of the gel-chromatography.